2011
DOI: 10.1080/14786435.2011.607139
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rhenium and ruthenium on the local mechanical properties of the γ and γ′ phases in nickel-base superalloys

Abstract: The effect of rhenium and ruthenium on the hardness of the γ' precipitates and the γ matrix in nickel-base superalloys was investigated using a nanoindenting atomic force microscope. The partitioning behaviour of the alloying elements and the lattice misfit between the γ and γ' phase were determined in fully homogenised samples to explain the alloying effects. Rhenium strongly strengthens γ as it predominantly partitions to γ and has a strong solid solution hardening effect. Ruthenium strengthens both γ and γ'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 26 publications
1
7
1
Order By: Relevance
“…As the exact size and shape of the tip are not known, the measurement on a reference minimizes the error involved in calculating the indentation modulus on the unknown sample. The hardness of the silicon tip with (100) orientation is reported to be in the range of 5-10 GPa [46,50] which is similar to the hardness values reported for the matrix (*6 GPa) and c 0 precipitate (9 GPa) in nickel-base superalloys [48]. These hardness values are of the same order or slightly less than the maximum pressure expected below the tip.…”
Section: Methodssupporting
confidence: 80%
“…As the exact size and shape of the tip are not known, the measurement on a reference minimizes the error involved in calculating the indentation modulus on the unknown sample. The hardness of the silicon tip with (100) orientation is reported to be in the range of 5-10 GPa [46,50] which is similar to the hardness values reported for the matrix (*6 GPa) and c 0 precipitate (9 GPa) in nickel-base superalloys [48]. These hardness values are of the same order or slightly less than the maximum pressure expected below the tip.…”
Section: Methodssupporting
confidence: 80%
“…Re was added to Ni-Co-W-Cr-Al-Ta alloys for improvement of the high temperature properties before. Research has been undertaken to understand the beneficial effects of Re [35][36][37][38][39][40] in such alloys. Earlier work indicated that Re formed clusters or segregated at the interfaces between the precipitates and the matrix.…”
Section: Alloy Considerationsmentioning
confidence: 99%
“…In the alloy, it is (Ni, Co) 3 (Al, Cr, Ti, Mo, Nb) [8] composition close to the stoichiometric [8]. Also, some excess (~0.5 %) of Co atoms is observed in the alloy that results in the formation of Со 3 Al phase having the DO 24 superstructure [4], which is suggested to be called as -phase.…”
Section: Samples After the Directional Crystallization (Original State)mentioning
confidence: 99%
“…The structural investigations of the original state of the alloy (after the directional crystallization) show that the multicomponent intermetallic -phase is the alloy base having L1 2 superstructure [1,4]. Its volume fraction is 0.78.…”
Section: Samples After the Directional Crystallization (Original State)mentioning
confidence: 99%
See 1 more Smart Citation